Random phage mimotopes recognized by monoclonal antibodies against the pyruvate dehydrogenase complex-E2 (PDC-E2). - Cha, S (1996)
Dihydrolipoamide acetyltransferase, the E2 component of the pyruvate dehydrogenase complex (PDC-E2), is the autoantigen most commonly recognized by autoantibodies in primary biliary cirrhosis (PBC). We identified a peptide mimotope(s) of PDC-E2 by screening a phage-epitope library expressing random dodecapeptides in the pIII coat protein of fd phage using C355.1, a murine monoclonal antibody (mAb) that recognizes a conformation-dependent epitope in the inner lipoyl domain of PDC-E2 and uniquely stains the apical region of bile duct epithelium (BDE) only in patients with PBC. Eight different sequences were identified in 36 phage clones. WMSYPDRTLRTS was present in 29 clones; WESYPFRVGTSL, APKTYVSVSGMV, LTYVSLQGRQGH, LDYVPLKHRHRH, AALWGVKVRHVS, KVLNRIMAGVRH and GNVALVSSRVNA were singly represented. Three common amino acid motifs (W-SYP, TYVS, and VRH) were shared among all peptide sequences. Competitive inhibition of the immunohistochemical staining of PBC BDE was performed by incubating the peptides WMSYPDRTLRTS, WESYPDRTLRTS, APKTYVSVSGMV, and AALWGVKVRHVS with either C355.1 or a second PDC-E2-specific mAb, C150.1. Both mAbs were originally generated to PDC-E2 but map to distinct regions of PDC-E2. Two of the peptides, although selected by reaction with C355.1, strongly inhibited the staining of BDE by C150.1, whereas the peptide APKTYVSVSGMV consistently inhibited the staining of C355.1 on biliary duct epithelium more strongly than the typical mitochondrial staining of hepatocytes. Rabbit sera raised against the peptide WMSYPDRTLRTS stained BDE of livers and isolated bile duct epithelial cells of PBC patients more intensively than controls. The rabbit sera stained all size ducts in normals, but only small/medium-sized ductules in PBC livers. These studies provide evidence that the antigen present in BDE is a molecular mimic of PDC-E2, and not PDC-E2 itself.